2012
DOI: 10.1675/063.035.0304
|View full text |Cite
|
Sign up to set email alerts
|

A Telemetry-based Study of Snowy Egret (Egretta thula) Nest-activity Patterns, Food-provisioning Rates and Foraging Energetics

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…The decrease in the number of trips to collect nest material during the breeding season is most likely associated with the water levels. Early in the season, whilst the nest is floating, the weight of the water soaked in the nest will pull the nest down, so constant maintenance is required (Buxton et al 1978;Maccarone et al 2012). When water levels decrease, the nest eventually rests on solid ground and little maintenance is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the number of trips to collect nest material during the breeding season is most likely associated with the water levels. Early in the season, whilst the nest is floating, the weight of the water soaked in the nest will pull the nest down, so constant maintenance is required (Buxton et al 1978;Maccarone et al 2012). When water levels decrease, the nest eventually rests on solid ground and little maintenance is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Shoebills are visual hunters (Möller 1982) and, therefore, are unlikely to capture prey and feed their chicks at night. The first early morning peak is probably the result of foraging around sunrise (Bryan et al 2005;Maccarone et al 2012) to provision the chick after a night without food. We were rarely able to identify prey species as the prey was regurgitated out of sight onto the nest or fed directly into the beak of the chick.…”
Section: Discussionmentioning
confidence: 99%
“…This weir has been the focus of previous studies on foraging behavior by Snowy Egrets (Egretta thula) and Great Egrets (Maccarone et al 2010). Most of the birds that feed at this weir breed in a large mixed-species colony 3 km to the west (Maccarone et al 2012).…”
Section: Study Site and Methodsmentioning
confidence: 99%
“…Aggressive interactions occur between Black-crowned Night-Herons and other species of wading birds, so the numbers of other herons and egrets also was recorded. Because marked Great and Snowy egrets return daily to this weir (Maccarone et al 2010(Maccarone et al , 2012, the same Black-crowned Night-Herons might also return repeatedly. Birds in this study were not marked, so it could not be determined if the same individuals were observed more than one time.…”
Section: Study Site and Methodsmentioning
confidence: 99%
See 1 more Smart Citation